Формування механізму економічної безпеки підприємств машинобудування щодо протидії рейдерству - Писаревський, Микола Ілліч (НТУ "ХПІ", 2017)
Метою статті є виділення на основі аналізу відомих методів та підходів до формування механізму забезпечення економічної безпеки та існуючого досвіду управлінської діяльності суттєвих характеристик та елементів механізму економічної безпеки підприємств машинобудування щодо протидії рейдерству, що дозволяє ідентифікувати процес його реалізації у вигляді цілісного комплексу складових. Вирішення поставлених у статті завдань здійснено за допомогою таких загальнонаукових та спеціальних методів дослідження: аналізу та синтезу, систематизації та узагальнення. У результаті дослідження розроблено концептуальну схему формування механізму забезпечення економічної безпеки, що дозволить ідентифікувати процес його реалізації за напрямками: діагностика та оцінка загроз економічній безпеці щодо протидії рейдерського захоплення; прийняття рішень щодо скорочення ймовірності рейдерського захоплення шляхом усунення відповідних загроз для забезпечення економічної безпеки; аналіз ефективності прийнятих рішень.

The purpose of the article is the selection on the basis of the analysis of known methods and approaches to the formation of the mechanism of providing economic security and the existing experience of management activities of the essential characteristics and elements of the mechanism of economic security of mechanical engineering enterprises in counteraction to raiding, which allowed to identify the process of its implementation as a holistic component of the components. Solving the tasks set in the article is carried out with the help of such general scientific and special research methods: analysis and synthesis, systematization and generalization. As a result of the study, a conceptual scheme for forming a mechanism for providing economic security has been developed that will identify the process of its implementation in the areas of: diagnosis and assessment of threats to economic security in countering raider hijacking; making decisions on reducing the probability of raider seizure by eliminating appropriate threats to ensure economic security; analysis of the effectiveness of the decisions taken. It is substantiated that the mechanism of economic security is a set of processes and actions of an organizational and economic nature with the help of methods, means and measures that, in conditions of unlawful seizure of enterprises (raiding), the actions of external and internal threats, create an opportunity to resist them, to maintain a stable functioning and development enterprises in time and space; The implementation of this approach will help to diagnose the state of the threat of raider seizure of the enterprise to form and select managerial decisions aimed at countering raider attacks.
Formation of the mechanism of economic security of mechanical engineering enterprises in response to raiding
Keywords: управлінська діяльність; зогрози; рейдерська діяльність; процес протидії; counteraction to raiding